Synergetic effect of thickness and oxygen addition on the electrochemical behaviour of tantalum oxide coatings deposited by HiPIMS in DOMS mode. (10th August 2022) - Alves, C.F. Almeida; Serra, R.; Bayat, R.; Ferreira, F.; Cavaleiro, A.; Carvalho, S.
Highlights: Ta1-x Ox based coatings were deposited by DOMS mode onto SS316L. Ta1-x Ox coatings exhibit a protective behaviour for polarisation-induced corrosion. Oxygen promotes morphology densification improving corrosion resistance. The corrosion resistance increases as a function of the immersion time. A more capacitive-like behaviour is observed as a function of the immersion time. Abstract: The HiPIMS technique in DOMS mode was used to deposit tantalum (Ta) and Ta1-x Ox films. After depositing pure metallic Ta and Ta1-x Ox films with two different thicknesses, their structure, morphology and chemical composition were investigated. Nano-indentation was used to evaluate the hardness of the films. OCP, potentiodynamic and EIS in artificial saliva at T = 37 °C were used to investigate the corrosion behaviour of the coatings. The results showed that, in the case of metallic coatings, increasing the film thickness, the β-phase becomes dominant over the α-phase, which compromised both the mechanical and electrochemical behaviours. Tantalum oxide films raised the polarisation resistance of the non-reactive coatings (metallic ones), exhibiting values 2–3 orders of magnitude higher.